IDENTIFYING LEARNERS LEARNING STYLES USING THE VARK MODEL - Tsevelmaa Demberel; Ulziihuyag Baasanjav (International Journal of Innovative Technologies in Social Science, 2025)
Understanding students' learning styles and personality traits is essential for creating effective learning strategies tailored to their needs and enhancing their ability to learn independently. Learning styles encompass various aspects of human cognition, perception, behavior, and cognitive traits that influence how students acquire, process, and retain information.To enhance the efficiency and effectiveness of educational interventions, educators must grasp each student's learning style and select teaching approaches that align with their individual characteristics. This not only enhances academic performance but also fosters student engagement, participation, and collaboration.While numerous learning style frameworks have been proposed in research, the VARK model (Visual, Auditory, Read/Write, Kinesthetic) stands out as a widely utilized, practical, and easily applicable model. According to the VARK model, students are categorized into visual, auditory, reading/writing, and kinesthetic learners based on their preferred mode of information intake.This research aims to identify students' learning styles, evaluate their impact on academic success, and explore avenues for optimizing instructional practices and enhancing learning outcomes.